A Study of Platelet Indices in Type 2 Diabetes Mellitus Patients: A Cross-Sectional Study Design - Shamal Iqbal, Kanwal Nazir Arbab, Maria Tasneem Khattak, Ambreen Ali, Alia Banori, Mehwish Iqbal Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of the study is to evaluate the reactivity of platelet parameters in a patient suffering from Type 2 diabetes mellitus. Place and duration of study: The study is conducted at Pak International Medical College Hayatabad Peshawar (PIMC) during march 2021 march 2022. Material and Method: Cross sectional hospital based study design is carried out on 300 diabetic patients having type 2 diabetes mellitus which is considered as a test group and compared with 300 normal blood glucose levels containing individuals which is considered as a control group. The blood samples of diabetes patients are analyzed under automated Hematology analyzer Sysmex XN-1000 and complete blood count of patients is analyzed with platelet parameters. Statistical software uses for the research test evaluation is SPSS Version 24. Results: The mean age in year of diabetic patients in this research study is 54.2+5.9 years and control group of patients having age in years is 54.5+ 5.3 years. Most of the sample patients in this study are suffering from type 2 diabetes mellitus. In this study, the number of males both in test and control group is 335(55.83%) and total number of females is 265(44.1%). In an Overall 300 patients lies in test group in this study, 127 are suffering from any other co-morbid conditions while 173 case samples are not suffering from any complicated state. Platelet parameters also compared between diabetic patients having complications or no complications, Mean of platelet indices are seen higher in diabetic patients having some other complications. The higher values of MPV, PDW and PLCR serve as an indicator in the initial complications of diabetes mellitus in humans and consider as a basic and inexpensive tool to analyze the vascular diseases and its related consequences. Conclusion: According to our study larger platelet formation and increase in volume of platelet indices causing prothrombotic state in diabetic patients and also develop diabetic vascular complications in an individual. Platelet parameters are considered as vital, clear, easy and non-expensive ways to analyze the thrombotic state in vascular disorders in diabetes patients. Keywords: Diabetes mellitus, Hematological findings, Glycated hemoglobin HbA1c, Mean platelet volume.